Associations between reproductive history, hormone use, APOE ε4 genotype and cognition in middle- to older-aged women from the UK Biobank - Lindseth, Linn R. S.; de Lange, Ann-Marie G.; van der Meer, Dennis; Agartz, Ingrid; Westlye, Lars T.; Tamnes, Christian K.; Barth, Claudia (Frontiers in Aging Neuroscience, 2023)
Introduction Relative to men, women are at a higher risk of developing age-related neurocognitive disorders including Alzheimer’s disease. While women’s health has historically been understudied, emerging evidence suggests that reproductive life events such as pregnancy and hormone use may influence women’s cognition later in life. Methods We investigated the associations between reproductive history, exogenous hormone use, apolipoprotein (APOE) ε4 genotype and cognition in 221,124 middle- to older-aged (mean age 56.2 ± 8.0 years) women from the UK Biobank. Performance on six cognitive tasks was assessed, covering four cognitive domains: episodic visual memory, numeric working memory, processing speed, and executive function. Results A longer reproductive span, older age at menopause, older age at first and last birth, and use of hormonal contraceptives were positively associated with cognitive performance later in life. Number of live births, hysterectomy without oophorectomy and use of hormone therapy showed mixed findings, with task-specific positive and negative associations. Effect sizes were generally small (Cohen’s d < 0.1). While APOE ε4 genotype was associated with reduced processing speed and executive functioning, in a dose-dependent manner, it did not influence the observed associations between female-specific factors and cognition. Discussion Our findings support previous evidence of associations between a broad range of female-specific factors and cognition. The positive association between a history of hormonal contraceptive use and cognition later in life showed the largest effect sizes (max. d = 0.1). More research targeting the long-term effects of female-specific factors on cognition and age-related neurocognitive disorders including Alzheimer’s disease is crucial for a better understanding of women’s brain health and to support women’s health care.